Accountability of Mantaa Duku’ in the Toraja Community - Natalia Paranoan; Erna Pasanda; Mira Labi Bandhaso; Anthon Paranoan; Carolus Askikarno Palalangan (Universitas Pendidikan Ganesha, 2024)
The purpose of this study is to reveal the meaning of accountability in the procession of Mantaa Duku' (distribution of buffalo meat) during the Rambu Solo ceremony (funeral ceremony) in Toraja, Indonesia. This research employs qualitative methods with an interpretive paradigm. Data collection was conducted through observation, in-depth interviews, and documentation involving seven informants. The researcher was directly involved in the daily activities of the informants to obtain valid data. The data was analyzed using the Miles and Huberman method and Ethnography methods to uncover the meaning of accountability in the Mantaa Duku’ procession. The results of this study indicate that the accountability of Mantaa Duku' activities in the Toraja community is centered on upholding the values of transparency, fairness, and responsibility. These values are integral to the community's social and cultural fabric, ensuring that the distribution of buffalo meat is conducted in a manner that reflects communal trust and ethical standards. The findings highlight the importance of cultural practices in shaping the understanding of accountability and demonstrate how traditional ceremonies can embody principles of good governance. This study contributes to the broader discourse on accountability by providing insights from a culturally specific context, emphasizing the role of traditional values in contemporary practices.